(3fNHI GdeSCdI TQM GdJMaI GdeQSdIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s; (3GdHQgGfHhQj , eMeO Hf aVd Gddg,J (B1029 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ GdeTJgQ HGHf GdfGHdSj gPG TQM dWja GdYHGQGJ hVYJg Ydi GdQSGdI GdJj UfagG GdTjN GdEeGe eMeO Hf GdTjN aVd Gddg GdgfOj s
(3BNQgG (B:s
(3aj efGRd GdbQGQ Edi eG jYLR Yfg GdebGd hgPG BNQ eG aJM Ydi ef GdJMQjQ hGdSdGe s
(3GdJMaI GdeQSdI ddHQgGfHhQi GfXQ GjVGM Gdecfhf L (B1 (3U`(B257s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B130s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B632s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds